Evaluating the role of relationship termination cost in measuring relationship quality in retail industry: a relationship marketing approach - Aziz, Md. Tareque (© 2014 ELK ASIA PACIFIC JOURNAL OF MARKETING AND RETAIL MANAGEMENT, 2016)
This article was published in ELK ASIA PACIFIC JOURNAL OF MARKETING AND RETAIL MANAGEMENT [© 2014 ELK's International Journal of Marketing] and the definite version is available at : http://www.elkjournals.com/MasterAdmin/UploadFolder/EVALUATING%20THE%20ROLE%20OF%20RELATIONSHIP/EVALUATING%20THE%20ROLE%20OF%20RELATIONSHIP.pdf The article website is at: http://www.elkjournals.com/